Comparative evaluation of IgG, IgM and IgA serum levels in patients with lichen planus referring to Tabriz Faculty of Dentistry - Masoumeh Mehdipour; Hosein Eslami; Ali Taghavi Zenooz; Zohreh Babaloo (مجله دانشکده دندانپزشکی اصفهان, 2013)
Introduction: Lichen planus (LP) is a relatively common chronic dermato-mucosal disease that affects the oral mucosa. The etiology and pathogenesis of LP is not fully understood. Some evidence indicates that humoral immunity may play a part in the development and progression of LP. This study was undertaken to evaluate the serum levels of immunoglobulins (IgG, IgM and IgA) in ulcerative and non-ulcerative OLP and compare them with a control group.Materials and Methods: In the present study 25 patients with ulcerative OLP, 25 patients with non-ulcerative OLP and 25 healthy individuals as the control group were evaluated. Serum levels of immunoglobulins were determined and one-way ANOVA was employed to compare mean differences, using SPSS 16 (α = 0.05).Results: According to one-way ANOVA mean levels of IgG in the ulcerative, non-ulcerative and control groups were 14.10 ± 1.76, 9.79 ± 1.67 and 8.48 ± 0.95, respectively, with higher levels of IgG in the ulcerative group compared to non-ulcerative and control groups (p value < 0.001). The mean IgM and IgA levels were not significantly different between the different groups under study (p value > 0.05).Conclusion: Based on the results of the present study, although increased levels of serum IgG were seen in patients with ulcerative lesions, there were no significant differences in serum levels of IgM and IgA between patients with ulcerated and non-ulcerative LP and healthy individuals. Key words: Immunoglobulins, Oral lichen planus, Serum